The contribution of observational studies in supporting the WHO 'treat all' recommendation for HIV/AIDS - Nathan Ford; Martina Penazzato; Marco Vitoria; Meg Doherty; Mary-Ann Davies; Elizabeth Zaniewski; Olga Tymejczyk; Matthias Egger; Denis Nash (Elsevier, 2018)
In 2015, the World Health Organization (WHO) recommended that all people living with HIV (PLWH) should start antiretroviral therapy (ART) irrespective of clinical or immune status. This recommendation followed almost 20 years of research into the clinical and population-level benefits and risks of starting ART early compared with deferring treatment. This article summarises the ways in which observational data support the work of WHO, including the support provided by the International epidemiology Databases to Evaluate AIDS (IeDEA), taking the example of 'treat all'.